Neural basis of attentional focus during endurance exercise - Bigliassi, M. (International Review of Sport and Exercise Psychology, 2021)
Controlling attention during endurance exercises can be a complex task for the human brain. This is mainly because internal bodily cues exert a major influence on one`s attentional focus during exercises performed at moderate and high intensities. Further understanding of the cerebral mechanisms that underlie attentional control during endurance tasks has the potential to imbue researchers with greater theoretical knowledge to investigate psychological and psychophysiological responses to exercise. In the present article, the author explores the neural basis of attentional focus during endurance tasks performed at various intensities. Compelling evidence indicates that subcortical regions such as the cingulate gyrus processes interoceptive signals relayed by the thalamus and recreate the sensations of discomfort. Consequently, the right dorsolateral prefrontal cortex may become active in order to partially assuage fatigue-related symptoms. The mechanisms described herein also indicate that frontal and parietal regions function in an orchestrated manner to prioritise processing of task-related information (e.g. distance covered) and prevent irrelevant signals from entering focal awareness during endurance tasks performed at moderate and high intensities.